FORMULASI TEPUNG JAGUNG, TEPUNG KULIT ARI KEDELAI DAN DAUN KELOR TERHADAP SIFAT KIMIA PADA BISKUIT SEBAGAI ALTERNATIF PENCEGAHAN DIABETES MELITUS - nur qomaria; Desty Muzarofatus Sholikhah; Sutrisno Adi Prayitno (Universitas Muhammadiyah Gresik, 2023)
Corn flour, soybean husk flour and moringa leaves are sources of food that have high protein and fiber content. The purpose of this study was to analyze the effect of biscuits with formulations of corn flour, soybean husk flour and Moringa leaves on macronutrient levels, crude fiber and water content. The research method was an experimental design with a completely randomized design (CRD) consisting of a control formula (F0) and 3 treatment formulas (F1, F2, F3). Laboratory tests were analyzed using the ANOVA (Analysis of Variance) test and the BNT follow-up test (Least Significant Difference). The test results of chemical properties of macronutrients, fiber and water content showed significant differences in sig values. 0.00. The macronutrient levels of F0, F1, F2, and F3 are 4.275 grams of protein; 5.4 grams; 6.54 grams; 9.105 grams, carbohydrates 12,372 grams; 13,017 grams ; 14,463 grams; 16,281 grams, fat 3,399 grams; 4.146 grams; 4.983 grams, ; 7.293 grams, fiber 1.026 grams; 1,869 grams; 2,412 grams; 3.708 grams, water content 1.755 grams; 1,998 grams; 3.06 grams; 4.212 grams. The conclusion of this study is that there is an effect of the formulation of corn flour, soybean husk flour and Moringa leaves on the chemical properties (protein, fat, carbohydrates, crude fiber and water content) in biscuit products.